The impossible fortune - Osman, Richard, 1970- (Osman, Richard, 1970- Thursday Murder Club mystery (Series), 2025)
"The unmissable new mystery in the Thursday Murder Club series from #1 New York Times bestselling author Richard Osman"-- Provided by publisher.